Lexin: Swedish-Tigrinya Dictionary - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish-Tigrinya dictionary for immigrants who want to learn Swedish. Includes everyday words and phrases as well as words from Swedish society.

text/xml

Svensk-tigrinskt lexikon. Lexikonet omfattar vanligt förekommande ord och fraser samt samhällsord som är viktiga för den som vill orientera sig i det svenska samhället.

text/xml
Lexin: Svensk-tigrinskt lexikon
Keywords: EVERYDAY LIFE; VARDAGSLIV; lexicon; lexikon; society; samhälle; lexin; lexin; Languages and Literature; Språk och litteratur